AKUNTANBILITAS PENGELOLAAN DANA DESA DI DESA LAWOLIA - Pramudiyas, Asrian; Sabarudin, Sabarudin; Chairunnas, Arnadi (Jurnal Akuntansi Kompetif, 2025)
Asrian pramudiyas 201830782 faculty of social sciences and economics accounting study program. accountability of village fund management in lawolia village guided by Mr. Sabarudin, SE., MM, AK and Arnadi Chairunnas, SE., M.Acc., Ak., CA., AFA as supervisor II. The purpose of this study is to examine the level of accountability in the management of village funds carried out by the lawolia village government in 2025 The type of research used in this study is descriptive research. with a qualitative approach. Descriptive research is a research method that focuses on describing solutions to actual problems by referring to the data collected. In addition, this study involves the process of presenting, processing, and interpreting data. (Achmadi, Abu and Cholid Narkubo, 2005). Accountability in the Management of funds allocated for villages (ADD) in Lawolia village has been carried out in accordance with applicable provisions. In the planning phase, the village has integrated the principles of participatory and transparent. Meanwhile, in the implementation phase, the principles of transparency and accountability are also implemented. Accountability is reflected in the availability of informative and clear data on the timing of the implementation of physical activity programs funded by ADD, which is supported by the existence of a notice board as a means of transparency in the use of these funds. Keywords: Pbb P2, Admission, Effectiveness